Skrb za samoga sebe i religioznost u formiranju identiteta i zadovljstva životom kod adolescenata i mladih Self-care and religiousness in the formation of identity and life satisfaction in adolescents and young people - Garmaz, Jadranka; Prović, Mihael (2021)
Vrijeme adolescencije i mladosti posebno je životno razdoblje, kad svaki pojedinac prelazi iz faze djetinjstva u jedno novo razdoblje skrbi za sebe, u kojem dolazi do formacije identiteta. U tom razdoblju svaka osoba zbog novih iskustava nanovo formira osobnu ljestvicu vrednota, u koju se uključuje i područje religioznosti, s vlastitim vrednotama i normama ponašanja. Autori u prvom dijelu rada opisuju nekoliko vidova skrbi o sebi te religiozni život adolescenata i mladih. Drugi dio rada posvećen je formaciji (religioznog) identiteta pod genetsko-biološkim i socio-kulturnim uvjetovanostima. Treći dio rada govori o zadovoljstvu životom adolescenata i mladih prema istraživanima Heinera Keuppa i Viere Pirker. Zaključuje se kako adolescenti i mladi preko različitih dimenzija religioznosti postižu osjećaj zajedništva i pripadnosti, te kako im povezivanje vlastitog životnog iskustva sa sadržajima vjere donosi zadovoljstvo životom.
The time of adolescence and youth is a special period of life in which each individual passes from the phase of childhood to a new period of self-care in which identity formation occurs. During this period, because of new experiences, each person re-forms the personal scale of values, which includes the area of religiosity with its own values and norms of behavior. In the first part of the paper, the authors describe several aspects of self-care and the religious life of adolescents and young people. The second part of the paper is dedicated to the formation of (religious) identity under genetic-biological and socio-cultural conditions. The third part of the paper talks about the life satisfaction of adolescents and young people according to the research of Heiner Keupp and Viera Pirker. It is concluded that adolescents and young people through different dimensions of religiosity achieve a sense of community and belonging, and that connecting their own life experience with the contents of faith brings them life satisfaction.
Bibliografija
Summary.
Keywords: adolescenti i mladi; skrb za sebe; formacija identiteta; religioznost; zadovoljstvo životom